ADSORBSI Fe DENGAN MENGGUNAKAN ZEOLIT ALAM SUATU USAHA UNTUK MENINGKATKAN MUTU MINYAK NILAM - Bhagus Alfiyan; Hamdillah Usman; Herry Santosa (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Patchouli oil quality could be determined by the amount of Fe impurity contained in. The presence of Fe in patchouli oil is an accomplished fact, nevertheless its presence, for some cases, isn’t desirable. Adsorption is a method to reduce the amount of Fe in patchouli oil. The research would be done beyond by two steps.  First step is preparation of active zeolite which consists of (1) reducing zeolite size into 80 mesh and (2) activating the zeolite. In this step, zeolite  will be immersed  into 250 ml  KMnO4 1 M solution during 24 hours then it will be dried  using   110-1200C oven during 30 minutes.  Second step is Fe adsorption in patchouli oil. The aim of adsorption step is to determine the most influencing independent variable among the weight of zeolit, adsorption temperature, and adsorption time using 2 levels Factorial Design Method. The adsorption will be done on 5 gr and 10 gr weight of zeolit, 300C and 900C adsorption temperature, along with 30 minutes and 60 minutes adsorption time.  The analysis of the amount of Fe that can be reduced will be done using Atomic Absorption Spectrofotometry (AAS) at the end of each variable. From experiment result, we have determined that the weight of zeolite is the most influencing independent variable to reduce Fe in patchouli oil.